1983
DOI: 10.1002/anie.198307211
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of a Linearly anti‐Annelated Tetracycloundecane. A Potential Precussor for a Coriolin Synthesis

Abstract: tion of 2,3-dimethyl-2-butene further confirmed its identity as lo2.After correction for differing sensitizer optical densities, the maximum intensities of 1and 2-sensitized '02 luminescence were compared. Since the quantum yield of triplet formation from 2 is 0.81[51, and this state is efficiently quenched by oxygen to form 'Oz[51, the absolute quantum yield of cercosporin-sensitized formation of 'Oz could be determined. Based on four independent determinations, the relative ratio of luminescence produced fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The product mixture could be used directly in the subsequent alkylation, in which 3a/3b yielded the single product 47, and 10a/10b were decomposed under the alkaline conditions. For the alkylation (of 3a/3b) and the oxidative cleavage (of 5) to 6')7'), conditions described earlier [6] for related transformations were applied. The intervening Birch reduction 4-Sa) was highly selective with respect to both the regiochemistry of the cyclopropane cleavage (opening between C(2) and C(8)) and the stereochemistry of the C(6) ketone reduction to the thermodynamically favored 'exo' hydroxyl group').…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The product mixture could be used directly in the subsequent alkylation, in which 3a/3b yielded the single product 47, and 10a/10b were decomposed under the alkaline conditions. For the alkylation (of 3a/3b) and the oxidative cleavage (of 5) to 6')7'), conditions described earlier [6] for related transformations were applied. The intervening Birch reduction 4-Sa) was highly selective with respect to both the regiochemistry of the cyclopropane cleavage (opening between C(2) and C(8)) and the stereochemistry of the C(6) ketone reduction to the thermodynamically favored 'exo' hydroxyl group').…”
mentioning
confidence: 99%
“…We have previously demonstrated that the use of the optically active forms of tricyc1o[3.3.0.0*~*]octan-3-one provides for a versatile synthetic approach to cyclopentanoid natural products [3] [5] [6], including one towards the total synthesis of coriolin, (-)-(9) [6]. Scheme 1 summarizes an alternative to this concept which is characterized by an unprecedentedly short route to the intermediate 8 in common with previous total syntheses of (f)-coriolin (9) [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation